Empowering citizen scientists to improve water quality: from monitoring to action - Warner, Stuart; Blanco Ramírez, Sara; de Vries, Sandra; Marangu, Nancy; Ateba Bessa, Henriette; Toranzo, Carla; Imaralieva, Madina; Abrate, Tommaso; Kiminta, Enock; Castro, José; de Souza, Marcelo Luiz; Ghaffar Memon, Abdul; et al. (Frontiers in Water, 2024)
Citizen science (CS) has so far failed to achieve its potential to contribute to water resource management globally despite a significant body of work proclaiming the benefits of such an approach. Also, this work has addressed concerns over precision, accuracy and reliability of methods used. This article presents the findings of a hackathon-type workshop challenge that brought together water quality experts and CS practitioners to explore barriers and possible solutions to mainstream citizen scientist-generated data into national, regional, and global reporting processes, and thereby provide a tangible connection between policy makers and community-based citizen scientists. We present the findings here as a perspective-type summary. This workshop challenge highlighted the breadth and scope of CS activities globally yet recognized that their potential for positive impact is going unrealized. The challenge team proposed that impact could be improved by: developing awareness; applying a simultaneous bottom-up / top-down approach to increase success rates; that local leaders or 'catalysts' are key to initiate and sustain activities; that generated data need to fulfil a purpose and create required information, and ultimately, lead to actions (data>information>action); recognizing that we are all potential citizen scientists is important; recognizing that 'good water quality' is subjective; and lastly that developing a communication gateway that allows bi-directional data and information transfer is essential.